7х-3-2х=х+9
5х-х=9+3
4х=12
х=3
13-(2х-5)=х-3
13-2х+5=х-3
-2х-х=-3-5-13
-3х=-21
х=7
3х-(10-9х)-22х - условие написано неверно
3х-10+9х-22х
-10-10х;
26-(17-2х)=5х
26-17+2х=5х
9=5х-3х
2х=97х-3-2х=х+9
5х-х=9+3
4х=12
х=3
13-(2х-5)=х-3
13-2х+5=х-3
-2х-х=-3-5-13
-3х=-21
х=7
3х-(10-9х)-22х - условие написано неверно
3х-10+9х-22х
-10-10х;
26-(17-2х)=5х
26-17+2х=5х
9=5х-3х
2х=9
F)17x-34=-170
17x = -170+34
17x=-136
x = -(136:17)
x = -8
Б)7+5=9x-11
-9x=-11-5-7
-9x=-23
x = (-23):(-9)
x = 2 5/9
В)5(х-6)=15(х-8)
5x-30=15x-120
5x-15x=-120+30
-10x=-90
x = (-90):(-10)
x = 9